P46 Predictors of short-term surgical complications after radical hysterectomy for early-stage cervical cancer. (1st November 2019) - Wenzel, H; van Gorp, T; Bekkers, R; de Kroon, C; van Lonkhuijzen, L; Massuger, L; Nijman, H; Smolders, R; van Trommel, N; Yigit, R; Zweemer, R; Kruitwagen, R; et al.
Abstract : Introduction/Background: Recently published data have renewed the debate on surgical approach (open vs. laparoscopic) in radical hysterectomy and its effect on survival and recurrence. In addition, an estimation of risk factors of surgical complications would be beneficial in the management of these patients. Therefore, we aimed to evaluate possible predictors of short-term surgical complications after radical hysterectomy for early-stage cervical cancer. Methodology: Patients diagnosed with cervical cancer FIGO (2009) stage IB1 and IIA1 between January 2015 and December 2017 who underwent radical hysterectomy with pelvic lymphadenectomy in one of the nine specialized centres in the Netherlands, were identified from the Netherlands Cancer Registry. Patients were excluded if primary treatment consisted of simple hysterectomy (i.e. without parametrial dissection) or radical trachelectomy. Complications and type of complications, developing within 30 days after surgery, were registered. Multivariable logistic regression analysis was used to identify predictors for surgical complications. Results: Of the 472 patients, 166 (35%) developed surgical complications. Predominant FIGO stage was IB1 (97%), mean age was 45±12 years, mean body mass index was 26±5 kg/m 2 . Most patients were treated with open surgery (58%). The most frequent complications were urinary retention with catheterisation in 73 patients (15%) and excessive perioperative blood loss >1000 mL (EBL) in 50 patients (11%) (table 1). Open surgery, chronic pulmonary disease, vascular disease and medical centre emerged as independent predictors of the occurrence of complications (table 2). BMI was found as negative predictor for urinary retention. Open surgery and BMI were found to be independent predictors for EBL. Conclusion: We conclude that open surgery, chronic pulmonary disease, vascular disease and BMI negatively affect the occurrence of short-term surgical complications. We believe these findings should also be taken into consideration, together with data on survival and recurrence, in the choice of surgical approach. Disclosure: None of the authors received financial support for the research and/or authorship of this article. Hans Wenzel - Nothing to disclose; Toon van Gorp - Nothing to disclose; Ruud Bekkers - Nothing to disclose; Cor de Kroon - Nothing to disclose; Luc van Lonkhuijzen - Nothing to disclose; Leon Massuger - Nothing to disclose; Hans Nijman - Grant Dutch Cancer Society; Stock owner SME Vicinivax; Grant Aduro; Ramon Smolders - Nothing to disclose; Nienke van Trommel - Nothing to disclose; Refika Yigit - Nothing to disclose; Ronald Zweemer - Proctor Intuitive Surgical; Roy Kruitwagen - Nothing to disclose; Maaike van der Aa - Nothing to disclose;